Genetic variants in the HER2 gene: Influence on HER2 overexpression and loss of heterozygosity in breast cancer. (March 2016) - Cresti, Nicola; Lee, Joanne; Rourke, Emma; Televantou, Despina; Jamieson, David; Verrill, Mark; Boddy, Alan V.
Abstract: Human epidermal growth factor receptor 2 (HER2) overexpression in breast cancer is an indicator of poor prognosis and is the pre-requisite for treatment with the agents targeting this member of the epidermal growth factor receptor family. In order to determine the influence of these common single-nucleotide polymorphisms (SNPs) in the HER2 gene, genomic DNA was obtained from 361 patients with breast cancer, aged between 29 and 82 years. Samples of tumour tissue were obtained from 241 (66%) patients and material for extraction of DNA is isolated from surrounding normal tissue by laser capture microdissection. Genotyping was performed using the Taqman fluorogenic 5′ nuclease assay. Of the 360 patients with definitive determination of HER2 status, 49% were positive. The Ile655Val SNP had no influence on the frequency of HER2 expression. However, the proline allele of the Ala1170Pro SNP was associated with a higher frequency of HER2 overexpression (56% versus 43%, p = 0.015). Where the germline genotype was homozygous, the tumour genotype was identical in every case and for both SNPs. In HER2-positive tumours, heterozygosity was maintained in only 15% and 18% of the Ile655Val and Ala1170Pro SNPs, respectively. This was lower than in the HER2-negative tumours (46% and 43%, respectively). Normal breast tissue (n = 23) retained the germline genotype in all but one case. The underlying link between the Ala1170Pro SNP and HER2 positivity is not known, nor is the significance of HER2 overexpression and loss of heterozygosity in breast cancer. However, these results illustrate the complexity of HER2 genotype and overexpression in this disease. Highlights: HER2 overexpression is more common in proline carriers of the Ala1170Pro SNP. Heterozygosity in HER2 SNPs was lost in more than 80% of HER2-positive tumours. Normal breast tissue retained the HER2 germline genotype in all but one case.